The rigidity bias - Risto Herrala (Bank of Finland, 2003)
We study the basic economic problem of choice between long-term and short-term commitments under a general characterization of uncertainty (aggregate uncertainty).When contingencies are contractible, a perfect market of Arrow-Debreau contingent claims implements the social optimum.When contingencies are not contractible, long-term commitments receive too much weight in individual portfolios.The economy as a whole is too rigid during periods of high aggregate shocks.The model links a rigidity bias with the operation of the price mechanism and the monetary system.
URN:NBN:fi:bof-20140807568
Keywords: G0; E0; 330; liquidity; central banking; monetary system